2022
DOI: 10.1186/s12864-021-08257-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome insights into the pharmaceutical and plant growth promoting features of the novel species Nocardia alni sp. nov

Abstract: Background Recent studies highlighted the biosynthetic potential of nocardiae to produce diverse novel natural products comparable to that of Streptomyces, thereby making them an attractive source of new drug leads. Many of the 119 Nocardia validly named species were isolated from natural habitats but little is known about the diversity and the potential of the endophytic nocardiae of root nodule of actinorhizal plants. Results The taxonomic status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 112 publications
0
4
0
Order By: Relevance
“…K (transcription) and E (amino acid transport and metabolism) play an important role in the growth and colonization of Nocardia , so they account for a relatively large proportion in all COG classification, whether in cloud gene, shell gene or core gene. 40 The core genome is different from the variable genome (cloud and shell genomes), representing genes that exist in all strains. In our study, core genome was enriched in “J: Translation, ribosomal structure and biogenesis” (48 genes), “S: Function unknown” (40 genes), “E: Amino acid transport and metabolism” (37 genes) and “K: transcription” (33 genes).…”
Section: Resultsmentioning
confidence: 99%
“…K (transcription) and E (amino acid transport and metabolism) play an important role in the growth and colonization of Nocardia , so they account for a relatively large proportion in all COG classification, whether in cloud gene, shell gene or core gene. 40 The core genome is different from the variable genome (cloud and shell genomes), representing genes that exist in all strains. In our study, core genome was enriched in “J: Translation, ribosomal structure and biogenesis” (48 genes), “S: Function unknown” (40 genes), “E: Amino acid transport and metabolism” (37 genes) and “K: transcription” (33 genes).…”
Section: Resultsmentioning
confidence: 99%
“…Strain ncl1 T was isolated from a surfaced sterilized root nodule of an Alnus glutinosa tree growing in Leazes Park, Newcastle upon Tyne, UK, as described by Nouioui et al ( 2022 ). An active culture of the strain was obtained following growth on yeast extract-malt extract agar (International Streptomyces project [ISP] medium 2 (Shirling and Gottlieb 1966 )).…”
Section: Methodsmentioning
confidence: 99%
“…Nocardia are well known as serious causal agents of progressive invasive infections of humans and animals, notably mycetoma and nocardiosis (Conville et al 2018 ), but are also seen to be successful saprophytes as they degrade complex organic compounds (Luo et al 2014 ), and as attractive sources of new drug leads (Männle et al 2020 ). Nocardia strains have been isolated from diverse ecological settings (Goodfellow and Maldonaldo 2012 ), notably from soil, sediments, sponges and wastewater treatment plants (Goodfellow and Maldonado 2012 ), as well as from coastal marine foams (Wright et al 2021 ) and healthy plant tissues (Kaewkla and Franco 2010 ), including nodules of actinorhizal plants (Ghodhbane-Gtari et al 2014 ) thereby suggesting they may be beneficial for plant growth (Nouioui et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous are the studies which reported the isolation of non-Frankia actinobacteria from actinorhizal root nodules 18,20,34,[37][38][39][40][41][42][43][44][45] as it was shown before for legume nodules which contain both rhizobial and non-rhizobial bacteria. 46,47 Three type strains; Micromonospora coriariae 42 ; Nocardia casuarinae 44 and Nocardia alni 48 have been isolated respectively from Coriaria; Casuarina and Alnus root nodules. Interestingly, a Micromonospora strain isolated in the present study is very closely related to M. coriariae species suggesting a widespread occurrence of members of this species within C. myrtifolia root nodules.…”
mentioning
confidence: 99%